USM Redefining World Class. - Ismail, Najua (Times Guides Sdn Bhd, 2008)
Professor Tan Sri Dato' Dzulkifli Abdul Razak,Vice Chancellor of Universiti Sains Malaysia (USM), may not strike one as a rebel. Well, not if one's idea of a rebel is a brooding red-jacketed teenager.